SYNTHESIS AND CHARACTERIZATION OF FUNCTIONALIZED VINYL COPOLYMERS I: STRUCTURE-MONOMER REACTIVITY RELATIONSHIP IN COPOLYMERS CONTAINING N-VINYL-2-PYRROLIDONE MOIETIES - GATICA,NICOLÁS (Sociedad Chilena de Química, 2005)
Copolymers containing N-vinyl-2-pyrrolidone as a common monomer with acrylic acid, 4-methyl styrene and vinyltrichlorosilane of different comonomer compositions were synthesized and characterized. Copolymer composition was determined by elemental analysis, from which monomer reactivity ratios (MRR, r) were estimated using straight line intersection procedures, such as Fineman-Ross and Kelen-Tüdõs methods, and a nonlinear one, the Reactivity Ratios Error in Variables Model. In this case, the values of MRR are rVP = 0.1 and rAA = 1.1 (for VP-co-AA), rVP = 0.8 and r4MS = 14.6 (for VP-co-4MS), and rVP = 0.0 and rVTCS = 0.3 (for VP-co-VTCS). Copolymers containing blocks of one of the monomer units and another tending to the alternation were obtained, with the product depending on the chemical nature of the comonomers. The different proposed comonomer distributions are analyzed in terms of the obtained MRR values and compared with related systems. The MRR are discussed in terms of monomer structural properties such as electronegativity and electron delocalization